Assessing the Impact of Maqasid Shariah on National Happiness Index: An Empirical Simulation in the Indonesian Context - Isnaini Harahap; Marliyah Marliyah; Chuzaimah Batubara; Khairina Tambunan; Early Ridho Kismawadi (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2026)
Happiness (falah) constitutes the ultimate objective of Islamic economics, encompassing both material prosperity and spiritual well-being within the framework of Maqāṣid al-Sharī‘ah. However, conventional welfare indicators—such as GDP and income—remain limited in capturing the moral, psychological, and social dimensions of human well-being. This study aims to empirically examine the contribution of the five dimensions of Maqāṣid al-Sharī‘ah—preservation of religion (ḥifẓ al-dīn), intellect (ḥifẓ al-‘aql), life (ḥifẓ al-nafs), progeny (ḥifẓ al-nasl), and wealth (ḥifẓ al-māl)—to Indonesia’s National Happiness Index. Using balanced provincial panel data covering 34 provinces across three observation periods (2014, 2017, and 2021), this research applies a Fixed Effects panel regression model, selected based on Chow and Hausman tests, to estimate the impact of each dimension. The findings indicate that ḥifẓ al-nafs (proxied by labor force participation) and ḥifẓ al-nasl (life expectancy) exert statistically significant but negative effects on happiness. In contrast, ḥifẓ al-dīn (zakat), ḥifẓ al-‘aql (literacy rate), and ḥifẓ al-māl (GRDP per capita) show positive but statistically insignificant relationships. These results suggest the presence of non-material trade-offs, where increased economic participation and demographic improvements do not necessarily translate into higher subjective well-being. The study provides empirical support for the argument that national happiness cannot be adequately explained by economic growth alone. Instead, it requires a multidimensional framework that integrates spiritual, social, and ethical dimensions, as emphasized in Islamic welfare theory. This research contributes to the literature by bridging Maqāṣid al-Sharī‘ah with empirical happiness measurement and offers policy implications for designing more holistic and value-based development indicators in Muslim-majority contexts.